2010
DOI: 10.1007/s10802-010-9391-4
|View full text |Cite
|
Sign up to set email alerts
|

Relational Aggression and Hostile Attribution Biases: Testing Multiple Statistical Methods and Models

Abstract: The present study used both categorical and dimensional approaches to test the association between relational and physical aggression and hostile intent attributions for both relational and instrumental provocation situations using the National Institute of Child Health and Human Development longitudinal Study of Early Child Care and Youth Development (M = 8.3 years-old, SD = 0.19, N = 840). A one standard deviation threshold was used to create categorical aggression status groups. In categorical analyses, chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
1
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 53 publications
4
31
1
5
Order By: Relevance
“…Furthermore, Mikami et al (2008) did not find an association between HAB and relational aggression in either adolescent girls who were diagnosed with ADHD or comparison adolescent girls. Finally, Godleski and Ostrov (2010) did not find an association between prior HAB for relational events and relational aggression in 6th grade. However, those categorized as high on both relational aggression and physical aggression demonstrated higher HAB for relational events, and girls showed higher HAB for relational events than boys.…”
Section: Relational Aggression and Hostile Attribution Biascontrasting
confidence: 58%
See 1 more Smart Citation
“…Furthermore, Mikami et al (2008) did not find an association between HAB and relational aggression in either adolescent girls who were diagnosed with ADHD or comparison adolescent girls. Finally, Godleski and Ostrov (2010) did not find an association between prior HAB for relational events and relational aggression in 6th grade. However, those categorized as high on both relational aggression and physical aggression demonstrated higher HAB for relational events, and girls showed higher HAB for relational events than boys.…”
Section: Relational Aggression and Hostile Attribution Biascontrasting
confidence: 58%
“…Previous studies have typically examined a main effect between HAB and relational aggression and have not assessed moderators other than gender. Thus, the absence of a link between HAB and relational aggression in previous research (e.g., Crain et al 2005;Godleski and Ostrov 2010;Mikami et al, 2008;Nelson et al 2008) may be due to the omission of relevant moderators. Our findings suggest that we must look beyond simple main effects to more complex interactions to gain a clearer picture of the association between HAB and relational aggression.…”
Section: Discussionmentioning
confidence: 88%
“…Through consulting, parents may also help adolescents to interpret, or make attributions, about others' behaviors. Hostile attributions have been extensively linked to children's and adolescents' physical (for a meta-analysis, see Orobrio de Castro, Veerman, Koops, Bosch, & Monshouwer, 2002) and, to a lesser extent, relational (e.g., Crick, Grotpeter, & Bigbee, 2002;Godleski & Ostrov, 2010) aggression. Similarities in parents' and children's tendencies to attribute hostile or benign intent to others' behavior have also been documented, suggesting that parents may transmit belief systems and understanding of others' intent to their children (e.g., MacBrayer, Milich, & Hundley, 2003;Nelson, Mitchell, & Yang, 2008;Werner, 2012), for example, during parent-child conversations about peers.…”
Section: Consultingmentioning
confidence: 99%
“…However, two other studies found no hostile attribution biases among relationally aggressive children (Crain, Finch, & Foster, 2005;Nelson, Mitchell, & Yang, 2008). Most recently, using a large, nationally representative sample, Godleski and Ostrov (2010) found that physical aggression, not relational aggression, was a unique predictor of children's hostile attributions in relational provocations. In contrast to previous results, children who made hostile attributions in instrumental conflicts became more relationally aggressive between Grades 3 and 6.…”
mentioning
confidence: 95%